EPEN-11. PROTEASOME AND HDAC INHIBITORS ARE CYTOTOXIC AGAINST RELA-FUSION PEDIATRIC EPENDYMOMA CELLS. (23rd April 2019) - Campagna, Marissa; Ma, Xiangjuan; McCarl, Lauren; Kumar, Rajeev; Broniscer, Alberto; Agnihotri, Sameer; Felker, James; Pollack, Ian; Kohanbash, Gary
Abstract: Ependymomas are the third most common pediatric brain tumor. Nine ependymoma subgroups have been described based on tumor location and genetics. Of supratentorial ependymomas, the C11orf95- RELA fusion (ST-EPN-RELA) subgroup is the most aggressive. The RELA encoded protein is an NF-κB transcription factor family member and activates NF-κB signaling. It has been reported that NF-κB and other pathways are important for ST-EPN-RELA tumors. We therefore hypothesized that ST-EPN-RELA cells may be sensitive to NF-κB signaling cascade inhibitors. To test our hypothesis we evaluated the cytotoxicity of multiple NF-kB signaling inhibitors on DKFZ-EP1NS RELA-fusion positive ependymoma cells and on our established patient-derived ST-EPN-RELA line (CPITT-1). Cells were treated with a single drug or combinations of drugs at concentrations ranging from 10 µM- 0.01 nM for 3–4 days and a WST-1 assay was used to assess viability. Of multiple inhibitors initially tested, Trichostatin A, a histone deacetylase (HDAC) inhibitor, in combination with MG-132, a proteasome inhibitor, displayed the highest level of cytotocity against both RELA-fusion lines. These findings led us to test clinically applicable drugs, including Marizomib, a brain penetrant proteasome inhibitor, and HDAC inhibitors, Panobinostat and Valproic acid. For DKFZ-EP1NS cells, the IC50 for Marizomib alone was 40.82 nM, Marizomib in combination with Panobinostat had an IC50 of 7.4 nM, and Marizomib in combination with Valproic Acid had an IC50 of 44.19. For CPITT-1 cells, the IC50 for Marizomib alone was 25.8nM, Marizomib in combination with Panobinostat had and IC50 of 3.07 nM, and Marizomib in combination with Valproic Acid had an IC50 of 27.04 nM. Overall, we observed that combination of proteasome and HDAC inhibitors are highly toxic to the RELA-fusion ependymoma cells tested. Further studies are warranted to evaluate the use these inhibitors for treating ST-EPN-RELA tumors.